Tetrahedral Framework Nucleic Acid Promotes the Treatment of Bisphosphonate-Related Osteonecrosis of the Jaws by Promoting Angiogenesis and M2 Polarization - Zhao, Dan; Cui, Weitong; Liu, Mengting; Li, Jiajie; Sun, Yue; Shi, Sirong; Lin, Shiyu; Lin, Yunfeng (ACS applied materials & interfaces, 2020)
Bisphosphonates are often used to treat osteoporosis, malignant bone metastases, and hypercalcemia. However, it can cause serious adverse reactions, bisphosphonate-related osteonecrosis of the jaw (BRONJ), which seriously affects the quality of life of patients. At present, the treatment of BRONJ is still difficult to reach an agreement, and there is no effective treatment. Therefore, it is very important to find effective treatments. Many studies have shown that the occurrence of BRONJ may be due to unbalanced bone turnover, anti-angiogenesis, bacterial infection, direct tissue toxicity, and abnormal immune function. The previous research results show that tetrahedral framework nucleic acids (tFNAs), a new type of nanomaterial, can promote various biological activities of cells, such as cell proliferation, migration, anti-inflammation and anti-oxidation, and angiogenesis. Therefore, we intend to explore the potential of tFNAs in the treatment of BRONJ through this study. The results show that tFNAs can promote the treatment of BRONJ by promoting angiogenesis and promoting M2 polarization in macrophages and inhibiting M1 polarization both in vitro and in vivo. These results provide a theoretical basis for the application of tFNAs in the treatment of BRONJ and also provide new ideas and methods for the treatment of other diseases based on ischemia and immune disorders.